Pengaruh Pembiasaan Menghafal Al Qur'an Surah Pendek Terhadap Karakter Siswa Kelas 5 di MI Takhasus Prapagkidul, Pituruh, Purworejo - Siti Mar’atul Badriya; Aniesatun Nurul Aliefah (IAINU Kebumen, 2026)
This research uses a quantitative approach where the respondents are students in classes 5A, 5B, 5C and 5D. Data collection techniques use questionnaires and documentation. The data analysis technique for this research uses instrument tests consisting of validity and reliability tests, classical assumption tests consisting of normality and linearity tests and hypothesis tests. Based on the research results, it can be concluded that: (1) students' habit of memorizing the Al Qur'an has an influence on the discipline character at MI Takhasus Prapagkidul. This is based on the results of the hypothesis test which shows that the sig. of 0.000 where the value is <0.005, so that it meets the criteria if Ha is accepted. Ha'adlah reads